2014
DOI: 10.1126/science.1243211
|View full text |Cite
|
Sign up to set email alerts
|

Break-Induced Replication Repair of Damaged Forks Induces Genomic Duplications in Human Cells

Abstract: In budding yeast, one-ended DNA double-strand breaks (DSBs) and damaged replication forks are repaired by break-induced replication (BIR), a homologous recombination pathway that requires the Pol32 subunit of DNA polymerase delta. DNA replication stress is prevalent in cancer, but BIR has not been characterized in mammals. In a cyclin E overexpression model of DNA replication stress, POLD3, the human ortholog of POL32, was required for cell cycle progression and processive DNA synthesis. Segmental genomic dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
385
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(417 citation statements)
references
References 41 publications
27
385
1
4
Order By: Relevance
“…One-ended breaks are recognized triggers of LTGC/BIR in yeast and in mammalian cells. 20,28,30,31,38 In response to an I-SceI-induced DSB, arrays containing 9 or more Ter sites resulted in progressive reductions in both STGC and LTGC,. With a larger Ter array, the distance between the I-SceI site and GFP sequences to the left of the Ter array increases (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One-ended breaks are recognized triggers of LTGC/BIR in yeast and in mammalian cells. 20,28,30,31,38 In response to an I-SceI-induced DSB, arrays containing 9 or more Ter sites resulted in progressive reductions in both STGC and LTGC,. With a larger Ter array, the distance between the I-SceI site and GFP sequences to the left of the Ter array increases (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,20 LTGC shares several properties with break-induced replication (BIR), a known mediator of genomic instability in yeast. [27][28][29][30][31] Indeed in BRCA1 mutant cells, LTGC is the most abundant HR product observed at Tus/Ter-stalled forks. Thus, determining the mechanisms underlying Tus/Ter-induced LTGC is crucial to understanding how the BRCA genes, and the HR machinery in general, suppress genomic instability at stalled replication forks.…”
Section: Introductionmentioning
confidence: 99%
“…Last, another mechanism by which RS could be involved on the generation of copy number alterations has also been recently described. This work revealed that break induced replication (BIR) is essential for cells to cope with RS induced by the overexpression of Cyclin E [39]. BIR is a specialized system of homologous recombination that can be used when the homology is limited to one side of the break, which is the case at a collapsed replication fork [40].…”
Section: Chromosomal Instability As a Results Of Replication Stressmentioning
confidence: 99%
“…For DNA synthesis, BIR employs the basic DNA replication machinery, but in addition it specifically depends on the DNA Polymerase accessory subunits POLD3 and POLD4. The reduction in the levels of either of these proteins in cells overexpressing Cyclin E reduces fork speed, increases fork collapse, blocks the generation of small amplifications and ultimately limits the proliferation of these cells [39]. To what extent POLD3 or POLD4 are non-essential in the context of primary cells demands further study.…”
Section: Chromosomal Instability As a Results Of Replication Stressmentioning
confidence: 99%
“…The POLD3 subunit interacts with the DNA polymerase clamp ring, called proliferating cell nuclear antigen (PCNA), which may also influence the processivity and fidelity of the four-subunit form. POLD3 was recently identified as a gene product that helps ameliorate the consequences of DNA breaks formed under replication stress conditions (16). This might be related to POLD3's role as a subunit of Pol δ, but now the potential role of Pol ζ in preventing break formation under stress conditions should be considered.…”
mentioning
confidence: 99%